PERAN MEDIASI KEUNGGULAN BERSAING PADA PENGARUH INTEGRASI INTERNAL DAN EKSTERNAL SUPPLY CHAIN DALAM UPAYA PENINGKATAN KINERJA USAHA KECIL MENENGAH - Edy Jumady; Hasbiyadi (Universitas Lambung Mangkurat, 2020)
The development of Makassar City SMEs continues to increase which makes Makassar City a fertile ground for investors to invest capital. This study aims to analyze how much influence (i) external and internal integration has on competitive advantage; (ii) external and internal integration of SMEs performance through competitive advantage; (iii) competitive advantage over the performance of SMEs; (iv) external and internal integration of SME performance is mediated by competitive finance. This research uses a quantitative approach sourced from the results of the questionnaire. The study population is small and medium business in the city of Makassar. The sampling method is probability random sampling with simple random sampling technique that is proportional random sampling for each of the SME sub-sector sectors. Data analysis technique used in this study is inferential description analysis and statistics, namely Generalized Structured Compenent Analysis (GeSCA). The results showed that external and internal integration variables had a significant effect on competitiveness, external integration had a significant effect on SME performance, competitiveness had a significant effect on SME performance, internal integration had a negative effect on SME performance, competitive advantage as a perfect mediator of influence between external integration and internal performance of SMEs.